The effects of compensation schemes on power delivery capabilities limited by voltage stability in transmission lines - Yukseler, N.H. (IEEE, 2002)
The effect of compensation on power delivery capabilities is studied from the point of view of voltage stability. Six different schemes using series and shunt compensation are investigated. Considering the effects of sending-end power factor, line loss, line length, and the degree of series and shunt compensation, numerical results are given for critical sending-end power, voltage, and angular separation. >